The application of liquid membrane waterproofing system for water tank work at kolej Pasir Salak / Nur Fatin Syamimi Mohd Afandi - Nur Fatin Syamimi, Mohd Afandi (2019)
Waterproofing is defined as the process of making an object or structure waterproof or water-resistant so that it will remains unaffected by water or resisting the ingress of water under specified conditions. Waterproofing is used in reference to building structures such as basement, flat roofs and wet areas. Modern items also can be waterproofed by applying water-repellent coatings. There are several components that will contribute to waterproofing system such as drainage composites that direct water away from structures, tie-ins between façade and foundation membranes. There are two types of waterproofing which is liquid membrane waterproofing and sheet mats waterproofing. In this case study, the topic chosen is The Application of Liquid Membrane Waterproofing System For Water Tank Work at Kolej Pasir Salak UiTM Seri Iskandar. In the application works, types of waterproofing used is liquid membrane. The liquid membrane used is a cement-based materials which is Sika Top Seal 107 Part A and Part B. The Sika Top Seal 107 Part A and Part B will be mixed very well to produce a good waterproofing. During the process of application works, there are several problems occurred such as narrow space and poor workmanship.